The concomitant use of ultra short beta-blockers with vasopressors and inotropes in critically ill patients with septic shock: A systematic review and meta-analysis of randomized controlled trials - Khalid Al Sulaiman; Hadeel A. Alkofide; Mashael E. AlFaifi; Sarah S. Aljohani; Abdullah F. Al Harthi; Rahaf A. Alqahtani; Ashwaq M. Alanazi; Lama H. Nazer; Abdulrahman I. Al Shaya; Ohoud Aljuhani (Elsevier, 2024)
Background: Septic shock is associated with systemic inflammatory response, hemodynamic instability, impaired sympathetic control, and the development of multiorgan dysfunction that requires vasopressor or inotropic support. The regulation of immune function in sepsis is complex and varies over time. However, activating Beta-2 receptors and blocking Beta-1 receptors reduces the proinflammatory response by influencing cytokine production. Evidence that supports the concomitant use of ultra short beta-blockers with inotropes and vasopressors in patients with septic shock is still limited. This study aimed to evaluate the use of ultra short beta-blockers and its impact on the ICU related outcomes such as mortality, length of stay, heart rate control, shock resolution, and vasopressors/inotropes requirements. Methods: A systematic review and meta-analysis of randomized controlled trials including critically ill patients with septic shock who received inotropes and vasopressors. Patients who received either epinephrine or norepinephrine without beta-blockers "control group" were compared to patients who received ultra short beta-blockers concomitantly with either epinephrine or norepinephrine "Intervention group". MEDLINE and Embase databases were utilized to systematically search for studies investigating the use of ultra short beta-blockers in critically ill patients on either epinephrine or norepinephrine from inception to October 10, 2023. The primary outcome was the 28-day mortality. While, length of stay, heart rate control, and inotropes/ vasopressors requirements were considered secondary outcomes. Results: Among 47 potentially relevant studies, nine were included in the analysis. The 28-day mortality risk was lower in patients with septic shock who used ultra short beta-blockers concomitantly with either epinephrine or norepinephrine compared with the control group (RR (95%CI): 0.69 (0.53, 0.89), I2=26%; P=0.24). In addition, heart rate was statistically significantly lower with a standardized mean difference (SMD) of -22.39 (95% CI: -24.71, -20.06) among the beta-blockers group than the control group. The SMD for hospital length of stay and the inotropes requirement were not statistically different between the two groups (SMD (95%CI): -0.57 (-2.77, 1.64), and SMD (95%CI): 0.08 (-0.02, 0.19), respectively). Conclusion: The use of ultra short beta-blockers concomitantly with either epinephrine or norepinephrine in critically ill patients with septic shock was associated with better heart rate control and survival benefits without increment in the inotropes and vasopressors requirement.